Use of computer graphics for visualization of communication network performance - Choo, Milton J. Sung Tong. (2009)
A graphical network management tool was created to aid the visualization of traffic on the Ethernet backbone of the mid-level network, Technet. Types of graphical visualization implemented includes graphs for bandwidth utilization according to the different basic network services and according to the different domains in Singapore. Other features include the abilities to superimpose the graphs of utilization of different protocols to give a feel of the relative load generated by each protocol, on-line debugging and collection of information for further off-line analysis.